Fungsi Daak Maraa’ dalam Upacara Hudo’ Kawit pada Masyarakat Suku Dayak Bahau di Kota Samarinda - Fajriansyah, Achmad Ali; Vivian, Yofi Irvan; Pratama, Zamrud Whidas (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
Daak maraa’ was presented in the context of the traditional activities of the Dayak Bahau tribe community that carried the ritual. Problems related to social aspects when daak maraa’ 'is not implemented, so it raises the assumption of how important daak maraa’ is for the Dayak Bahau people. This study aims to: explain the musical structure of the Hudo’ Kawit ceremonies held by the Dayak Bahau people in Samarinda; describe the function of daak maraa’ presented at the Hudo’ Kawit ceremony for the Dayak Bahau community in Samarinda. This research uses a qualitative methodology by applying observation techniques, data collection, and data analysis. Observation techniques include the object of research that is the focus of research. Data collection techniques are based on literature study, informants, interviews, and documentation. Analysis techniques by reducing data and concluding. Research results in accordance with the background of the problem and objectives. The musical structure and function have a connection, that the application of rhythmic sound daak maraa’ is presented as a accompaniment to rituals and prayers. The application of daak maraa’ is actualized with a static rhythm, namely: (a) sukat 4/4; (b) tempo (andantino) 78-83; (c) motive (literal); (d) dynamics (forte); (e) timbre (teng, pliers, tung, and dung). The research findings contain a value that the function of daak maraa’ is present and applied as an anticipation goal on the basis of the potential for bad sound (yog) which can come to disrupt and cancel the traditional ceremonial activities. Yog is believed to exist by the Dayak Bahau tribe based on legend over folk prose stories that are thought to have taken place in the real world and are bad (magi).